2003
DOI: 10.1038/sj.bjc.6601175
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of breast cancer in premenopausal women

Abstract: Physical activity appears to be inversely related to risk of breast cancer, yet the results remain inconsistent. To evaluate this relation among premenopausal women and examine variation in risk according to level of obesity and use of oral contraceptives (OCs), the authors examined data from the Nurses' Health Study II. During 10 years of follow-up, 849 cases of invasive premenopausal breast cancer were confirmed. Physical activity was assessed by self-report at baseline and during follow-up using a validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 31 publications
(19 reference statements)
2
60
1
Order By: Relevance
“…HRs for hormone receptor-defined invasive breast cancer according to level of recreational physical activity within the previous 4 years Contrary to most studies, which have not found that the relation between physical activity and breast cancer risk was modified by weight changes before inclusion (9,11,13,21,30), three articles report that the risk decrease associated with baseline physical activity is restricted to postmenopausal women with limited weight gain between youth and baseline (22,31,32). However, a weight gain before baseline may be associated with a decrease in physical activity after baseline (33).…”
Section: Discussionmentioning
confidence: 60%
“…HRs for hormone receptor-defined invasive breast cancer according to level of recreational physical activity within the previous 4 years Contrary to most studies, which have not found that the relation between physical activity and breast cancer risk was modified by weight changes before inclusion (9,11,13,21,30), three articles report that the risk decrease associated with baseline physical activity is restricted to postmenopausal women with limited weight gain between youth and baseline (22,31,32). However, a weight gain before baseline may be associated with a decrease in physical activity after baseline (33).…”
Section: Discussionmentioning
confidence: 60%
“…Recent reviews concluded that physical activity both at young ages and in adulthood reduced the risk of breast cancer; IARC (2002) and Lagerros et al (2004). However, subsequent findings concerning premenopausal breast cancer are inconsistent, both for physical activity at young ages (Dorn et al, 2003;Steindorf et al, 2003;Yang et al, 2003;Margolis et al, 2005) and around diagnosis (AdamsCampbell et al, 2001;Gilliland et al, 2001;Matthews et al, 2001;Colditz et al, 2003;Dorn et al, 2003;Hirose et al, 2003;John et al, 2003;Steindorf et al, 2003;Yang et al, 2003;Margolis et al, 2005). Without evidence from a formal meta-analysis using individual data from all relevant studies, it is difficult to interpret the available results.…”
Section: Discussionmentioning
confidence: 99%
“…Although an expert group convened by the International Agency for Research on Cancer concluded that there was sufficient evidence that physical activity reduced the risk of premenopausal breast cancer (IARC, 2002), results from more recent studies have been contradictory (Adams-Campbell et al, 2001;Gilliland et al, 2001;Matthews et al, 2001;Colditz et al, 2003;Dorn et al, 2003;Hirose et al, 2003;John et al, 2003;Steindorf et al, 2003;Yang et al, 2003;Margolis et al, 2005).…”
mentioning
confidence: 99%
“…Physical activity has been shown to reduce risk of breast cancer (1)(2)(3)(4)(5)(6). Studies have suggested that total activity, lifetime recreational activity, nonrecreational activity, and vigorous activity may be important components of activity that influence breast cancer risk (2,3,6,7).…”
Section: Introductionmentioning
confidence: 99%